Hidden harvest: U.S. benefits from international research aid - Pardey, Philip G.; Alston, Julian M.; Christian, Jason E.; Fan, Shenggen (International Food Policy Research Institute, 1996)
This report spells out the benefits to the United States from its partnership with the CGIAR. Using wheat and rice to illustrate the gains from international research on important food crops, the report shows that U.S. investments in CGIAR wheat and rice research have paid off many times over for U.S. farmers--Pref.